2018
DOI: 10.12688/f1000research.11881.1
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting immune cell metabolic machinery for functional HIV cure and the prevention of inflammaging

Abstract: An emerging paradigm in immunology suggests that metabolic reprogramming and immune cell activation and functions are intricately linked. Viral infections, such as HIV infection, as well as cancer force immune cells to undergo major metabolic challenges. Cells must divert energy resources in order to mount an effective immune response. However, the fact that immune cells adopt specific metabolic programs to provide host defense against intracellular pathogens and how this metabolic shift impacts immune cell fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 90 publications
1
28
0
Order By: Relevance
“…As the primary mode of action of metformin involves a decrease in cellular respiration induced by a mild and specific inhibition of the respiratory chain complex 1 (NADH: ubiquinone oxidoreductase) in the mitochondria, 4 it is possible that its impact on NCR expression stems from its ability to alter the cellular metabolism of CD4 T cells. In line with the increasing interest in targeting immuno-metabolism for HIV cure and the prevention of chronic HIV-associated inflammation, 5 the finding that metformin leads to a decrease in NCR coexpressing CD4 T cells is of possible interest in both areas. Studies by our group and others have identified PD1 and TIGIT expressing and coexpressing CD4 T cells as highly enriched for integrated HIV DNA and strongly associated with the size of the viral reservoir even after adjusting for nadir and current CD4 T cells.…”
Section: Discussionmentioning
confidence: 99%
“…As the primary mode of action of metformin involves a decrease in cellular respiration induced by a mild and specific inhibition of the respiratory chain complex 1 (NADH: ubiquinone oxidoreductase) in the mitochondria, 4 it is possible that its impact on NCR expression stems from its ability to alter the cellular metabolism of CD4 T cells. In line with the increasing interest in targeting immuno-metabolism for HIV cure and the prevention of chronic HIV-associated inflammation, 5 the finding that metformin leads to a decrease in NCR coexpressing CD4 T cells is of possible interest in both areas. Studies by our group and others have identified PD1 and TIGIT expressing and coexpressing CD4 T cells as highly enriched for integrated HIV DNA and strongly associated with the size of the viral reservoir even after adjusting for nadir and current CD4 T cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, HIV infection also induces the expression of different components of inflammasomes in GALT (46), and both the immune regulation and delayed progression to AIDS were associated with a particular activation phenotype of T cells in GALT from HIC (47). Furthermore, in HIV infection immune activation and inflammation were also associated with immunometabolism reprogramming through the use of glucose and fatty acids (48). In whole blood, we observed an enrichment of gluconeogenesis and lipid metabolism pathways in differentially expressed genes between HIC and cART patients, but it was not possible to determine whether there was activation or inhibition of these pathways.…”
Section: Discussionmentioning
confidence: 99%
“…While the newest generation of antiretroviral drugs is associated with reduce toxicity, metabolic abnormalities persist in those on treatment [ 30 ]. Emerging evidence suggests that these metabolic abnormalities interact with immune cells to drive immune dysfunction and persistent inflammation [ 33 , 34 ]. Future studies should focus on unraveling these complex interrelationships to identify new therapeutic targets that limit inflammation and improve outcomes in HIV patients on ART.…”
Section: Discussionmentioning
confidence: 99%
“…Factors driving these abnormalities include not only the effects of the drugs themselves but also the effects of chronic inflammation, the irreversible damage of metabolic tissues sustained prior to the introduction of ART, host genetic risk, side effects associated with other medications, age-related factors, obesity and lifestyle/behaviour (diet, exercise, and smoking) [ 31 , 32 ]. Emerging evidence suggests that these metabolic abnormalities may further affect immune function and contribute to the development of non-AIDS-associated comorbidities [ 33 , 34 ]. Consistent with these findings, immunometabolic signatures that combine markers of immune activation/inflammation and metabolite profiles have been shown to be strong predictors of frailty [ 35 ], hepatic dysfunction [ 36 ], neurocognitive impairment [ 37 ], and depression [ 38 ] in HIV patients on ART.…”
Section: Introductionmentioning
confidence: 99%